2022
DOI: 10.3390/buildings12060804
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on FabLab Environments and Creativity: Implications for Design

Abstract: Fabrication laboratories (FabLabs) and makerspaces are used to transform ideas into tangible products. Used in a design–learning context, they can enhance cognitive and creative skills. Creativity is the pivotal ability to produce innovative outcomes in makerspaces, and several studies have attempted to understand the role of makerspaces and creativity in specific fields. However, a comprehensive study offering a holistic view of the contributions of the makerspaces as built environments that foster creativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Makerspaces and digital fabrication are ideal environments to encourage and develop substantial aspects of creativity. These include person, product (design outcome), environment (physical and social), as well as process aspects of creativity (Soomro et al, 2022(Soomro et al, , 2023. Furthermore, digital fabrication spaces also contribute to fostering creative competence (Taheri et al, 2020) and creativity in co-design activities (Choi et al, 2022).…”
Section: Creativity and Digital Fabricationmentioning
confidence: 99%
“…Makerspaces and digital fabrication are ideal environments to encourage and develop substantial aspects of creativity. These include person, product (design outcome), environment (physical and social), as well as process aspects of creativity (Soomro et al, 2022(Soomro et al, , 2023. Furthermore, digital fabrication spaces also contribute to fostering creative competence (Taheri et al, 2020) and creativity in co-design activities (Choi et al, 2022).…”
Section: Creativity and Digital Fabricationmentioning
confidence: 99%
“…Creativity refers to a person communicating a "new concept (which is the product). Mental activity (or mental process) is implicit in the definition, and of course no one could conceive of a person living or operating in a vacuum, so the term press is also implicit" (Rhodes, 1961, p. 305), one of the most wellknown definition, cited by many researchers, such as Soomro et al (2022). This means a person interacts with the press (a collective element based on Hofstede's cultural dimension theory), shaping his/her own individual culture (included in the individual element based on Hofstede's cultural dimension theory), as illustrated in Figure 1.…”
Section: Relationship Between Culture and Creativitymentioning
confidence: 99%
“…In addition, their research revealed that design-build education fosters innovation, creativity, and entrepreneurship in engineering. Studies have demonstrated that FabLabs and makerspaces have a good impact on the self-expression, inspiration, motivation, and creative capacities of their users through the provision of encouraging and supportive physical and social environments [15].…”
Section: Fostering Creativity Through Motivational and Inspiring Lear...mentioning
confidence: 99%